2013
DOI: 10.1186/1471-2458-13-692
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between bacteriological quality of dug-wells, hygiene behaviour and well characteristics in two cholera endemic localities in Douala, Cameroon

Abstract: BackgroundAccess to potable water is grossly inadequate in Douala-Cameroon. The situation is worse in slum areas, compelling inhabitants to obtain water from sources of doubtful quality. This has contributed to frequent outbreaks of water-borne diseases particularly cholera, which results in severe morbidity and mortality. Shallow wells are a major source of water in these areas. We analyzed the influence of some factors on the bacteriological quality of well water in Bepanda and New Bell, cholera endemic loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 19 publications
5
31
0
9
Order By: Relevance
“…The detection of Antimicrobial Resistant (AMR) bacteria in borehole water has been reported in South Africa (8,39), Cameroon (40), and Denmark (34). In one such study, Ateba et al reported the presence of isolates that were resistant to chloramphenicol, vancomycin, oxytetracycline, amoxicillin, erythromycin, and sulfamethoxazole (8).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…The detection of Antimicrobial Resistant (AMR) bacteria in borehole water has been reported in South Africa (8,39), Cameroon (40), and Denmark (34). In one such study, Ateba et al reported the presence of isolates that were resistant to chloramphenicol, vancomycin, oxytetracycline, amoxicillin, erythromycin, and sulfamethoxazole (8).…”
Section: Microbiological Analysismentioning
confidence: 99%
“…3 Evidence on the positive effect of point-of-use treatment on water quality, and significant reductions in diarrheal diseases among its users, exists. [4][5][6][7][8][9][10][11] The usage of chlorine products has been described as one effective and easy-to-use means of water disinfection. Likewise, the protective effect of solar-disinfected water against cholera infections in small children has been shown and could serve as an alternative point-of-use treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…11,15,16 Kepentingan terhadap perilaku memakai air bersih menjadi dasar pertimbangan seseorang untuk berniat melakukan sesuatu. Jika ia menganggap apa yang akan dilakukannya penting maka pada tahap selanjutnya ia akan mempunyai niat yang didukung oleh sikap, norma yang dipersepsikan, dan kondisi personalnya.…”
unclassified
“…17 Niat dan hambatan lingkungan berpengaruh terhadap perilaku menmpergunakan air bersih di tatanan rumah tangga. [8][9][10]15,16 Hambatan lingkungan terhadap perilaku penggunaan air bersih memiliki nilai yang baik pada semua responden. Masyarakat yang berasumsi bahwa lingkungan Tamansari memang sudah kumuh dan air yang mereka dapat dari sumur bor maupun gali lebih mudah dan murah terjangkau.…”
unclassified
See 1 more Smart Citation